2020
DOI: 10.3389/fmicb.2020.588841
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriome-Associated Endosymbiotic Bacteria of Nosodendron Tree Sap Beetles (Coleoptera: Nosodendridae)

Abstract: The family Nosodendridae is a small group of tree sap beetles with only 91 described species representing three genera from the world. In 1930s, bacteria-harboring symbiotic organs, called bacteriomes, were briefly described in a European species Nosodendron fasciculare. Since then, however, no studies have been conducted on the nosodendrid endosymbiosis for decades. Here we investigated the bacteriomes and the endosymbiotic bacteria of Nosodendron coenosum and Nosodendron asiaticum using molecular phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…The genus name Shikimatogenerans refers to its ability to perform the shikimate pathway. Previous studies have shown that there might be other closely related Bacteroidetes bacteria associated with other beetle families 42 , 66 , 67 . Thus, we propose silvanidophilus as species name to indicate that this symbiont is associated with beetles of the family Silvanidae.…”
Section: Resultsmentioning
confidence: 99%
“…The genus name Shikimatogenerans refers to its ability to perform the shikimate pathway. Previous studies have shown that there might be other closely related Bacteroidetes bacteria associated with other beetle families 42 , 66 , 67 . Thus, we propose silvanidophilus as species name to indicate that this symbiont is associated with beetles of the family Silvanidae.…”
Section: Resultsmentioning
confidence: 99%
“…This benefit probably extends to many other beetles in which tyrosine-provisioning microbes have been identified, including S. oryzae , P. infernalis and E. postfasciatus ( Vigneron et al, 2014 ; Anbutsu et al, 2017 ; Anbatsu and Fukatsu, 2020 ; Kuriwada et al, 2010 ) as well as many other weevils harbouring intracellular symbionts ( Zhang et al, 2017 preprint). In addition, symbionts localised in bacteriomes have been described for at least five additional beetle families (Brentidae, Bostrichidae, Nosodendridae, Throscidae and Dasytidae), and the close phylogenetic relationships of some Brentidae symbionts with Nardonella ( Zhang et al, 2017 preprint) and of the Bostrichidae and Nosodendridae symbionts with Shikimatogenerans ( Engl et al, 2018 ; Hirota et al, 2020 ) suggest that these symbionts may be functionally similar ( Salem and Kaltenpoth, 2022 ). Hence, symbioses in insects can have multifaceted phenotypic impacts beyond immediate nutritional effects, and studying these more comprehensively will provide us with a better understanding of the implications of symbiotic interactions on the ecology and evolution of insects.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the Bostrichidae are thus far unique in containing species that harbor two Bacteroidota endosymbionts, which are closely related but diverged to metabolically complementary symbionts. This finding highlights the versatile nature of symbioses with Bacteroidota bacteria that are emerging as widespread beneficial symbionts across at least four beetle families (Silvanidae: (Engl et al, 2018;Hirota et al, 2017), Coccinellidae: (Hurst et al, 1996;Hurst, Bandi, et al, 1999), Nosodendridae (Hirota et al, 2020), and Bostrichidae: this study and Engl et al 2018) as well as at least two other insect orders (Bandi et al, 1995;Engl et al, 2018;. The repeated independent acquisitions of these specific clades of Bacteroidota symbionts suggest that these bacteria were once specialized in establishing lasting infections in insects, akin to Wolbachia (Kiefer et al, 2022) or Sodalis (McCutcheon et al, 2019).…”
Section: Discussionmentioning
confidence: 83%
“…The genus name Shikimatogenerans refers to its ability to perform the shikimate pathway. Previous studies have shown that closely related Bacteroidota bacteria are also associated with other beetle families such as the Silvanidae and the Nosodendridae (Engl et al, 2018; Hirota et al, 2020). Thus, we propose bostrichidophilus as a species epithet to indicate that this symbiont clade is associated with beetles of the family Bostrichidae.…”
Section: Resultsmentioning
confidence: 99%